2018
DOI: 10.1002/ar.23909
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model for Cilia‐Associated Cardiovascular Anomalies with a High Penetrance of Total Anomalous Pulmonary Venous Return

Abstract: Primary cilia are small organelles projecting from the cell surface of various cell types. They play a crucial role in the regulation of various signaling pathway. In this study, we investigated the importance of cilia for heart development by conditionally deleting intraflagellar transport protein Ift88 using the col3.6-cre mouse. Analysis of col3.6;Ift88 offspring showed a wide spectrum of cardiovascular defects including Double Outlet Right Ventricle and Atrioventricular Septal Defects. In addition, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Additional sites of Cre mTmG/LacZ activity in the rat 3.6kb‐Col1a1‐Cre line include the neural tube, ectoderm, neuroepithelium, hindlimb buds, foregut endoderm, walls of the dorsal aortae, and virtually all cell layers constituting the future heart (E8.5). ( 132,236 ) Germline transmission was observed in both lines. Another rat 3.6kb‐Col1a1‐Cre line generated by Zha et al ( 133 ) showed Cre LacZ activity in calvaria, trabecular bone, and osteocytes (P10).…”
Section: Cre Mice Targeting Osteoblastsmentioning
confidence: 91%
See 1 more Smart Citation
“…Additional sites of Cre mTmG/LacZ activity in the rat 3.6kb‐Col1a1‐Cre line include the neural tube, ectoderm, neuroepithelium, hindlimb buds, foregut endoderm, walls of the dorsal aortae, and virtually all cell layers constituting the future heart (E8.5). ( 132,236 ) Germline transmission was observed in both lines. Another rat 3.6kb‐Col1a1‐Cre line generated by Zha et al ( 133 ) showed Cre LacZ activity in calvaria, trabecular bone, and osteocytes (P10).…”
Section: Cre Mice Targeting Osteoblastsmentioning
confidence: 91%
“…Tables 1–6 list the Cre lines discussed and include references of documents describing Cre activity in bone and off‐target sites, and original articles reporting the lines (knock‐in–based Cre lines in these tables are labeled with an asterisk). ( 22‐213 )…”
Section: Introductionmentioning
confidence: 99%
“…Loss of function mutants of IFT genes also display cardiac malformations. For example, Ift88 mutant mice show defects in cardiac OFT septation, ventricular trabeculation, AVSD, and cardiac cushion EMT, with no localization of the Hh pathway transcription factor Gli2 in cardiac cilia (Burns et al, 2019;Clement et al, 2009;Willaredt et al, 2012). In a previous study, Washington Smoak et al (2005) reported that Shh deletion results in abnormal migration of neural crest cells, contributing to arch artery and OFT septation defects.…”
Section: 2mentioning
confidence: 99%
“…In recent years, the insight into the pathogenesis of AVSDs has significantly changed. Studies from a number of different groups have implicated abnormal development of the SHF-derived DMP in the pathogenesis of pASDs, i.e., the most common single septal defect in virtually all forms of AVSDs [2][3][4]10,13,14,[21][22][23]. Understanding of the molecular mechanisms that govern DMP development has steadily developed over the last 10 years.…”
Section: Of 21mentioning
confidence: 99%